Urban park and educational benefits of ecosyste\m: case study of Taman Perbandaran Pulau Pinang - Hamzan, Nur Ashiqin; Abdul Rahim, Asyirah (2015)

(untitled)
The potential of urban parks in providing education on ecosystem is important as a mean to increase socio-ecological well-being. Sustainable development requires the quality and sustenance of the socio-ecological system which pose a need for knowledge on how ecosystems fulfil social needs. This dependence can be described in the operational definition of ecosystem in providing services, benefits or products to meet human needs, directly or indirectly, which occurred along natural processes and ecosystem structure known as ecosystem services. Hence, the importance of education on ecosystem services to ensure socio-ecological well-being. The article intends to identify ecosystem services that can be found in the urban park and identify potential educational activities to be established in the urban park. Firstly, observations were used to map and identify ecosystem services of the park. Secondly, purposive sampling with two sets of semi-structured interview with 100 urban park visitors and five representatives from five focus groups. The results show that the ecosystem in Taman Perbandaran Pulau Pinang is able to provide benefits to humans in terms of supporting services, regulating services, provisioning of services and cultural services to the users. These services can be used in educational activities to improve knowledge on the importance of ecosystem for social well-being. At present, only labels indicating plants’ name are available at the park. Therefore, other forms of ecosystem educational activities could be established in cooperation with various stakeholders and the park management to further enhance the functions of the urban park ecosystem landscape. In summary, urban parks provide educational benefits to urban communities through reinforcing knowledge of ecosystem services that are important for social well-being.